IMPLEMENTASI TRANSAKSI PEMBIAYAAN GRIYA DALAM PERSPEKTIF FIKIH MU’AMALAH DI BANK SYARIAH INDONESIA KANTOR CABANG PEMBANTU SITUBONDO - Ach. Afin; R. Fakhrurrazi (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2022)
At this time there are many emerging Islamic banking with the many developments of sharia. The birth of Islamic financial institutions in Indonesia brings an interesting competitive atmosphere in the banking business discourse. In addition to the presence of conventional banks, our society is now presented with alternative options to invest their funds, of course through the presence of Islamic banking services. Islamic banking services offer products with a different scheme from conventional banks. In accordance with the title